The Effects of Prenatal Yoga for Primagravida with Gen Expression mRNA FKBP5 (FK506-binding Protein 51) - Ruqaiyah1,2, Nusratuddin Abdullah3 , Mochammad Hatta4 , Nasrudin A Mappeware5 , Ayatullah Harun 2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: FKBP5 protein plays an important role in determining sensitivity to negative glucocorticoidfeedback, a key mechanism for stopping the HPA axis response in stressful episodes.Methods: The design of this study is a quasi-experimental approach / quasi experimental and one groupdesign pre and post test design with group control. The sample in this study amounted to each group of 12respondents as control and treatment of yoga.Results: There was a significant difference (p = 0.000 <?) on average FKBP5 gene expression in the controlgroup before (7.1 ± 0.59) and after observation (9.43 ± 0.68), meaning that there was an increase in cortisollevels in the control group in the control group before and after observation, while the treatment groupshowed a significant difference (p = 0.001 <?), the average expression of FKBP5 gene before being treated(7.52 ± 0.49) and after being treated (6.88 ± 0.54),Conclusion: There was a significant difference (p = 0.000 <?) on average FKBP5 gene expression in thecontrol group, which means that prenatal yoga decreased FKBP5 gene expression before and after treatment.